(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study aimed to evaluate the acute toxicity of the butanol extract obtained from the aerial parts of Lagochilus setulosus. The plant material was collected in Tashkent in 2024 and taxonomically identified at the Institute of the Chemistry of Plant Substances, Uzbekistan. The crude methanol extract was fractionated successively with chloroform, ethyl acetate, and n-butanol to obtain the test sample. Acute toxicity was assessed on outbred white male mice (19–21 g) under laboratory conditions. The extract was administered orally at doses of 500, 1000, 3000, 8000, 10000, and 12000 mg/kg. The animals were monitored for 14 days to record behavioral changes and mortality. The median lethal dose (LD₅₀) was calculated using the Litchfield–Wilcoxon method. The results showed dose-dependent toxic effects. At lower doses, an increase in locomotor activity and heart rate was observed, while higher doses led to depression of the central nervous system, reduced motor activity, shallow respiration, tremor, and mortality. The LD50 value of the butanol extract was determined to be 10600 mg/kg (9217–12190 mg/kg). According to GOST 12.1.007-76 and A.V. Stefanov’s classification, the extract is classified as low-toxic (Class III) and practically non-toxic (Class V).